Effect of different media, temperature, pH on the growth of Macrophomina phaseolina (Tassi) Goid causing root rot of sesame: Effect of different media, temperature, pH on the growth of Macrophomina phaseolina (Tassi) Goid causing root rot of sesame - M SURYA PRAKASH REDDY; M SANTHA LAKSHMI PRASAD; R D PRASAD; JAYANT BHATT (Journal of Oilseeds Research, 2020)
Among fungal diseases, stem root rot or charcoal rot caused by Macrophomina phaseolina (Tassi) Goid is widely distributed and highly destructive disease of sesame. Different synthetic media were tested to select suitable media for the growth of M. phaseolina. Among them, oat meal agar, malt dextrose, Elad and Chet medium showed significantly high mycelial growth at 120 hrs. The maximum growth of M. phaseolina was observed at 30, 35 and 40°C which indicates preference towards higher temperatures and also maximum growth recorded at 5 and 7 pH. Extracts of safflower, mustard, sunflower, groundnut, soybean and sesame amended in media have shown more mycelial growth of M. phaseolina while castor stem extract recorded lowest growth.